Evaluation of Mathematics Education Curriculum in Terms of Product on the Context, Input, Process, and Product Model - Natalia, Stevi; Purba, Santri Chintia; Darhim, Darhim; Situmeang, Gita Meilisa (IndoMath: Indonesia Mathematics Education, 2023)
This research aims to reveal the results of curriculum evaluations that refer to the Indonesian National Qualifications Framework. The assessment form uses the context, input, process, and product model, but this paper will only examine the product section analysis. This research is evaluation research with a qualitative approach. Data collection techniques used observation, questionnaires, and interviews, then validated using triangulation, namely methods, sources, and expert group discussion forums. This study was analyzed using the Miles and Huberman model, including data reduction, presentation, and conclusions. The results of the product section evaluation are as follows 1). The learning achievement of 3 aspects successfully achieved cognitive by 75%, practical at 75.51%, and psychomotor at 74.12%. 2). 99% of students have a Semester Grade Point Average that meets the criteria, and 3). 85.8% of graduates managed to get jobs according to the curriculum.